1929
DOI: 10.1037/h0070967
|View full text |Cite
|
Sign up to set email alerts
|

The relative potency of color and form perception at various ages.

Abstract: The purpose of this experiment l was to determine whether the perception of color or the perception of form plays a major part in the total apprehension of an object by individuals of a given age and whether this relative potency tends to change with age. The method employed was a modification of that used in a similar study carried out by Descoudres 2 and published in 1914. It involves the setting up of an experimental situation in which the subjects are required to choose between two alternatives in matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
64
0

Year Published

1969
1969
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(75 citation statements)
references
References 0 publications
11
64
0
Order By: Relevance
“…The ordering of dimensions: shape > shading > size, agrees with findings on cue salience in the literature. It has long been known that, for adults, form is more salient than color, and shading is, in effect, a variation between the colors of black and white (Brian & Goodenough, 1929). In addition, these two dimensions appear to be more salient than size.…”
Section: Resultsmentioning
confidence: 99%
“…The ordering of dimensions: shape > shading > size, agrees with findings on cue salience in the literature. It has long been known that, for adults, form is more salient than color, and shading is, in effect, a variation between the colors of black and white (Brian & Goodenough, 1929). In addition, these two dimensions appear to be more salient than size.…”
Section: Resultsmentioning
confidence: 99%
“…Most early research (e.g., Bills, 1931;Brian & Goodenough, 1929;Gails, 1922) tested the intuitive differential-practice account for CatteU's observation (cf. Quantz, 1897, p. 10).…”
mentioning
confidence: 99%
“…Unfortunately, the existence of this developmental change is still unsubstantiated. The evidence PATRICK AND OFFENBACH for such a change has come from work by Brian and Goodenough (1929) and others (e.g., Corah, 1964;Suchman & Trabasso, 1966); they reported that children younger than 3 years and older than 5 years preferrred form (the others preferred color). Modreski and Goss (1969) and Offenbach (1983;Offenbach, Baecher, & White, 1973) failed to find the predicted developmental changes among 4-and 5-year-old children.…”
mentioning
confidence: 99%
“…For example, there may be a shift in preference (or dominance or attention) during the preschool years from color to form (e.g., Brian & Goodenough, 1929;Modreski & Goss, 1969). Specific attention to one of these cues could interact with classification criteria to change or alter sorting behavior.…”
mentioning
confidence: 99%